2014
DOI: 10.5664/jcsm.4114
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Sleep Behavior in Normal Infants during the First Year of Life

Abstract: Study Objectives: To longitudinally examine sleep patterns, habits, and parent-reported sleep problems during the fi rst year of life. Methods: Seven hundred four parent/child pairs participated in a longitudinal cohort study. Structured interview recording general demographic data, feeding habits, intercurrent diseases, family history, sleep habits, and parental evaluation of the infant's sleep carried out at 1, 3, 6, 9, and 12 months Results: Nocturnal, daytime, and total sleep duration showed a high inter-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
82
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 35 publications
15
82
2
3
Order By: Relevance
“…Approximately half of the parents (54.71%) reported that their infant's sleep is a problem, a finding in line with previous investigations demonstrating that sleep is a highly prevalent concern for parents of young children (Porter & Ispa, ; Sadeh et al., ; Teng et al., ). Specific sleep behaviours that differentiated parents who would consider their infant sleep a problem included increased wake after sleep onset, shortened parental reported longest sleep period and increased numbers of nighttime wakings, an observation consistent with prior studies on correlates and predictors of sleep problems during infancy (Bruni et al., ; Byars et al., ; Sadeh et al., ). We found that infants with sleep problems and those with uncertain sleep conditions had similar parental reported sleep patterns.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Approximately half of the parents (54.71%) reported that their infant's sleep is a problem, a finding in line with previous investigations demonstrating that sleep is a highly prevalent concern for parents of young children (Porter & Ispa, ; Sadeh et al., ; Teng et al., ). Specific sleep behaviours that differentiated parents who would consider their infant sleep a problem included increased wake after sleep onset, shortened parental reported longest sleep period and increased numbers of nighttime wakings, an observation consistent with prior studies on correlates and predictors of sleep problems during infancy (Bruni et al., ; Byars et al., ; Sadeh et al., ). We found that infants with sleep problems and those with uncertain sleep conditions had similar parental reported sleep patterns.…”
Section: Discussionsupporting
confidence: 81%
“…By the time the child reaches 6 months of age, the average total 24‐hour sleep duration decreases from 14.6‐12.9 hr and daily nocturnal awakenings reduce from 1.7‐0.8 times (Galland, Taylor, Elder, & Herbison, ), with large individual variability being reported (Bruni et al., ; Mindell et al., ). Infant sleep patterns that do not meet the developmental trends or fail to meet parental expectations are commonly reported as problematic and can include a wide range of behaviours such as bedtime struggles, prolonged periods to fall asleep, frequent night wakings, sleep fragmentations and shortened sleep duration (Bruni et al., ; Byars, Yolton, Rausch, Lanphear, & Beebe, ; Sadeh et al., ). Parental perception of child's sleep as a severe problem has been found to be associated with parental worries, anxiety and nighttime feeding involvement (Thunstrom, ).…”
Section: Introductionmentioning
confidence: 99%
“…Neonates sleep for an average of 16 h per day, decreasing to 14 h per day by 6 months, usually a longer sleep overnight and a number of naps through the day . Sleep patterns stabilise between 6 and 12 months, with establishment of adult‐type architecture (including REM) at this age …”
Section: Sleepingmentioning
confidence: 99%
“…9 Sleep patterns stabilise between 6 and 12 months, with establishment of adult-type architecture (including REM) at this age. 9,10 Sleep hygiene for infants is controversial, with two traditional paradigms of 'parent-led' or 'baby-led' care. Neither has a particularly robust evidence base, and a mix of the two is the best approach to suggest at present.…”
Section: Sleepingmentioning
confidence: 99%
“…In children, sleep–wake regulation and sleep states evolve rapidly during the first year of life with a continuous maturation throughout childhood. Sleep troubles such as frequent sleep‐onset difficulties, frequent night waking and short sleep quantity affect 20%–30% of children during the first 3 years of life (Al Mamun et al., ; Bruni et al., ; Morgenthaler, Owens, Alessi, & Swick, ). Moreover, longitudinal studies suggested that these troubles may persist later in childhood, and even during adolescence and adulthood (Al Mamun et al., ; Byars, Yolton, Rausch, Lanphear, & Beebe, ; Morgenthaler et al., ; Quach, Hiscock, Canterford, & Wake, ).…”
Section: Introductionmentioning
confidence: 99%